Analysis and application of evolutionary markers in the epidemiology of Mycobacterium tuberculosis - Van der Spuy, Gian Dreyer (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Biomedical Sciences. Molecular Biology and Human Genetics))--Stellenbosch University, 2008.